Penggunaan D-Optimal Mixture Design untuk Optimasi dan Formulasi Self-Nano Emulsifying Drug Delivery System (SNEEDS) Asam Mefenamat - Yandi Syukri; Bambang Hernawan Nugroho; Istanti Istanti (Fakultas Farmasi Universitas Andalas, 2020)
This study aimed to optimize and formulate the poorly water-soluble mefenamic acid in the self-nano emulsifying drug delivery system (SNEDDS) using D-optimal mixture design. The initial screening was carried out to determine phases of the oil, surfactants, and co-surfactants used to prepare the ternary phase diagram. D-optimal mixture design was used to optimize SNEDDS loading mefenamic acid by selecting SNEDDS composition as an independent factor and SNEDDS characterization as a response. SNEDDS in the optimal formula were characterized, including transmittance, particle size, polydispersity index (PDI), and zeta potential. Oleic acid, Tween 80, and polyethylene glycol (PEG) 400 were the selected oil, surfactant, and co-surfactant phases for their greatest ability to dissolve mefenamic acid. The optimization results showed that the optimal formula was that using 10% oleic acid, 80% of Tween 80, and 10% of PEG 400. SNEDDS loading mefenamic acid produced nanoemulsion with 88.5% of transmittance, 190.03 ± 1.18 nm of particle size, 0.469 ± 0.03 of PDI, and -44.1 ± 1.69 mV of zeta potential. This study concludes that the D-optimal mixture design can be used to optimize and prepare the SNEDDS loading poorly-water soluble mefenamic acid.